2019
DOI: 10.1158/1078-0432.ccr-18-4099
|View full text |Cite
|
Sign up to set email alerts
|

Clonotypic Diversity of the T-cell Receptor Corroborates the Immature Precursor Origin of Cutaneous T-cell Lymphoma

Abstract: Purpose: Mycosis fungoides is one of the most common types of extranodal T-cell lymphomas, considered to be caused by malignant transformation of the mature T cells residing in the skin. However, some clinical observations such as the multifocal distribution of mycosis fungoides lesions or patterns of relapse after radiotherapy are not readily explainable by the mature T-cell origin theory.Experimental Design: We have performed a detailed analysis of T-cell receptor (TCR) rearrangements in single malignant cel… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
30
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 58 publications
3
30
0
1
Order By: Relevance
“…It is likely that such ancestor clones may become extinct during the progression of the tumor and are no longer detectable, a phenomenon which was described during the evolution of another highly heterogeneous tumor, the glioblastoma. 44 Finally, we would like to propose a model for the pathogenesis of MF that accounts for the previously found clonotypic heterogeneity [19][20][21] and the ITH described here (Fig 7) . ITH is readily detectable in ESP, which testifies to the history of mutational tumor evolution before seeding of neoplastic cells in the skin.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…It is likely that such ancestor clones may become extinct during the progression of the tumor and are no longer detectable, a phenomenon which was described during the evolution of another highly heterogeneous tumor, the glioblastoma. 44 Finally, we would like to propose a model for the pathogenesis of MF that accounts for the previously found clonotypic heterogeneity [19][20][21] and the ITH described here (Fig 7) . ITH is readily detectable in ESP, which testifies to the history of mutational tumor evolution before seeding of neoplastic cells in the skin.…”
Section: Discussionmentioning
confidence: 63%
“…By analysing the repertoire of T-cell receptor (TCR) sequences in malignant cells in MF, we found that even early lesions, such as patches and plaques, show a considerable level of clonotypic diversity which occurs via seeding of early precursors in the skin. [19][20][21] It is conceivable that those malignant clonotypes differ with respect to their mutational history and provide material for ITH in MF. In this study we were able to confirm the existence of extensive subclonal heterogeneity in MF.…”
Section: Introductionmentioning
confidence: 99%
“…We have recently shown that MF cells sampled from a plaque or a tumor may share the same TCRγ clonotype but exhibit different TCRβ and TCRα clonotypes 20,21 . Since TCRγ loci ( TCRG ) rearrange before TCRβ ( TCRB) and TCRα ( TCRA) and the unique TCRG CDR3 sequences are inherited by the T-cells derived from those early clones, these findings are incompatible with the current model of mature T-cell as precursor of MF where all malignant cells would share an identical clonotype for all rearranged TCR genes ( TCRG , TCRB and TCRA) .…”
Section: Introductionmentioning
confidence: 99%
“…24 Indeed, using more careful experimental approaches such as tumor fraction enrichment by laser capture microdissection and analysis of purified lymphocytes or mononuclear cells from the blood, some authors were able to find clonal, circulating cells even in early stages of disease development. 20,[25][26][27][28] Unfortunately, due to the difficulties in PCR amplification of TCRB and TCRA from genomic DNA these findings rely heavily on the analyses of TCRγ, which may give false positive results because of the low diversity of TCRG .…”
Section: Introductionmentioning
confidence: 99%
“…Mycosis fungoides (MF) is the most common type of cutaneous T-cell lymphoma (CTCL) (1) that develops from clonotypically diverse malignant T-cell precursors seeding the skin (2,3). Prognosis in the early stages (T1-T2, patches and plaques) is excellent, however the development of tumours (T3) or erythroderma (T4) is associated with a significant decrease in survival (4,5).…”
Section: Introductionmentioning
confidence: 99%